2018
DOI: 10.1186/s12889-018-5101-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stunting among children living in an urban slum of Bangladesh: findings of a prospective cohort study

Abstract: Background: Bangladesh is one of the 20 countries with highest burden of stunting globally. A large portion (around 2.2 million) of the population dwells in the slum areas under severe vulnerable conditions. Children residing in the slums are disproportionately affected with higher burden of undernutrition particularly stunting. In this paper, findings of a prospective cohort study which is part of a larger multi-country study are presented. Methods: Two hundred and sixty five children were enrolled and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
67
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 64 publications
(56 reference statements)
8
67
0
8
Order By: Relevance
“…The relationship between birthlength and child development through stunting The result of this study showed that there was a significant relationship between birth-length and child development through stunting. This study was supported by Islam et al, (2018), who stated that a child with short birth-length has greater risk to the occurence of stunting at 12-24 months old.…”
Section: The Relationship Between Currentsupporting
confidence: 61%
“…The relationship between birthlength and child development through stunting The result of this study showed that there was a significant relationship between birth-length and child development through stunting. This study was supported by Islam et al, (2018), who stated that a child with short birth-length has greater risk to the occurence of stunting at 12-24 months old.…”
Section: The Relationship Between Currentsupporting
confidence: 61%
“…On average, HEU infants experienced a decline of 0.55 LAZ during the first year. The magnitude of this decline is lower than recent cohorts of HEU children in sub‐Saharan Africa noting a −1.00 to −1.50 change in z‐score in the first year (Islam et al, ; MAL‐ED Network Investigators, ; Sudfeld et al, ; Webb et al, ). Mean LAZ at 12 months in this analysis (−0.96) was half that of the Kenya national average at the same age (−1.80; C. G. Victora et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…This cohort may have had more engagement in health care relative to the general population due to the monthly clinic visits, which included regular counselling on infant nutrition and health, and free infant formula. The prevalence of stunting in the general population increases with age and appears to peak at 24 months of age (Islam et al, ; MAL‐ED Network Investigators, ; C. G. Victora et al, ). Thus, our rates of stunting may be lower because we did not follow children to 24 months during the peak of stunting prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn anthropometric outcomes such as low birthweight (LBW), stunting at birth, and small for gestational age (SGA) are highly prevalent in low‐ and middle‐income countries. In Bangladesh, the prevalence of LBW in 2012–2013 was 20% (Khan et al, ), prevalence of newborn stunting in various studies is of similar magnitude (Islam et al, ; Klemm et al, ; Mridha et al, ), and SGA is very common (e.g., 67.3% of infants born to mothers who received iron and folic acid during pregnancy, as stated in Klemm et al, ; Mridha et al, ). Birth length has been shown to be associated with compromised cognitive development (Lee et al, ), and LBW and restricted intrauterine growth have been linked with other longer term outcomes such as attained height, achieved schooling/education, and income later in life (Victora et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…Fetal growth restriction is a major public health problem worldwide (Black et al, ) and particularly in Bangladesh (Christian et al, ; Islam et al, ; Khan, Islam, Awan, & Muurlink, ; Klemm et al, ; Mridha et al, ). Newborn anthropometric outcomes such as low birthweight (LBW), stunting at birth, and small for gestational age (SGA) are highly prevalent in low‐ and middle‐income countries.…”
Section: Introductionmentioning
confidence: 99%